(untitled) (Malay Literature, 2017)
Leadership is the ability of a government in shaping the people’s mind to achieve goals that have been planned together in order to strengthen its administration especially in establishing diplomatic relations with other countries. Without the mobilization of intellectual and physical cooperation from these two groups, it is impossible for a government to succeed in its diplomatic missions. Therefore, this article will discuss the leadership of the Malay Sultanate in establishing diplomatic relations through data analysis of the events described in historiographic manuscripts such as Sulalat al-Salatin, Al-Tarikh Salasilah Negeri Kedah, Hikayat Merong Mahawangsa and Tuhfat al-Nafis. In addition, this article also describes the effectiveness of this leadership in response to the diplomatic relations that had been initiated by and accepted from other governments. The result of the study will show that a variety of methods or approaches were used by the rulers of the Malay Sultanate in advancing the government’s reputation from the economic, social and physical aspects. Keywords: leadership, leaders/rulers, Malay Sultanate, diplomatic, historiography